Antimicrobial effect of Carboxy Methyl Cellulose (CMC) containing aqueous and ethanolic Eucalyptus camaldulensis L. leaves extract against Streptococcus pyogenes, Pseudomonas aeruginosa and Staphylococcus epidermidis - Alizadeh Behbahani, Behrooz; Tabatabaei Yazdi, Farideh; Mortazavi, Ali; Gholian, Mohammad Mahdi; Zendeboodi, Fatemeh; Vasiee, Alireza (Archives of Advances in Biosciences, 2014)
Oil from the eucalyptus tree (Eucalyptus camaldulensis L.) is used today in many over the counter cough and cold products, to relieve congestion. Eucalyptus oil is also used in creams and ointments to relieve muscle and joint pain, and in some mouthwashes. In this study Eucalyptus camaldulensis leaves extracted with water and ethanol 96°and the antimicrobial effects of extracts were evaluated by “using the method of Collins” and “disk agar diffusion method”. Antimicrobial properties of Carboxy Methyl Cellulose (CMC) films containing 20, 40, 60, and 80 mg/ml concentration of the extract studied against on Streptococcus pyogenes PTCC 1447, Pseudomonas aeruginosa PTCC 1310 and Staphylococcus epidermidis PTCC 1435. The results showed that aqueous and alcoholic extract were quite effective in 2000 μg/ml concentration on Streptococcus pyogenes and Staphylococcus epidermidis and have inhibition effect, while both extracts have no certain antimicrobial effect on Pseudomonas aeruginosa. Minimum Inhibitory Concentration (MIC) of ethanolic extract of Eucalyptus camaldulensis leaves were performed for each microorganism. Minimal Bactericidal Concentration (MBC) for bacteria was performed using the dilution method. The edible films containing mangrove extract presented more effective impact on the growth of Streptococcus pyogenes than Pseudomonas aeruginosa (p<0.05). The result indicates extracts of Eucalyptus camaldulensis leaves have the greatest effect on gram-positive bacterium Streptococcus pyogenes. As a result, aqueous and ethanloic extracts of Eucalyptus camaldulensis leaves, have been strong antimicrobial activity against many food pathogen bacteria